Human T Lymphotropic virus-1 associated gastrointestinal histoplasmosis in Peru - Carlos Canelo-Aybar; Jose Cuadra-Urteaga; Fernando Atencia; Franco Romani (Journal of Infection in Developing Countries)
We report a 72-year-old patient with chronic diarrhoea and histologic evidence of gastrointestinal histoplasmosis. He had no history of HIV or of taking immunosuppressive drugs. The patient was found to be a carrier of Human T-lymphotropic virus-1, a condition associated with inflammatory, lymphoproliferative, and opportunistic infectious diseases. To our knowledge, there are only three previous cases reporting this coinfection and this is the first documented case with gastrointestinal involvement.